Leprosy and Social Determinants of Health in South Brazil: Geographically evaluated analysis (Research, Society and Development, 2021)
Objective: to verify the relationship between leprosy and geographic space, taking into account social determinants of health and using a tool that allows the analysis of these relationships locally. Methodology: Ecological study, carried out in an endemic city in southern Brazil. The geocoding of the cases was conducted and socioeconomic variables of interest were selected. After descriptive analysis, we followed with the spatial correlation through the Bivariate Moran Index, followed by Linear Regression. For the variables present in the selected model, the Geographically Weighted Regression was applied using the ArcGis software version 10.5.1. Subsequently, the results were specialized using thematic maps. Results: Regarding socioeconomic and clinical-operational characteristics, there was a greater number of male cases (55.3%), aged 16 to 60 years (69.3%), white race (67.8%), multibacillary cases (80.9%), borderline clinical form (45.2%) and disability grade I (62.6%). The spatial analysis showed an average incidence of 1.19 cases/10,000 inhabitants, in each census sector. Regarding social determinants, the characteristics are heterogeneous in space, and agglomeration of inhabitants showed a direct association with leprosy, as well as race/brown color, characterizing as risk factors in the most evident regions. On the other hand, literacy had an inverse relationship, associating an increase in literacy with a reduction in the occurrence of the disease. Conclusion: Social determinants in health help to explain the heterogeneity of disease distribution. Understanding this relationship is essential to direct prophylaxis and control actions.